The Little Book of External Debt 2006 - World Bank (World Development Indicators, 2006)
This first edition of The Little Book on External Debt provides a quick reference for users interested in external debt stocks and flows, major economic aggregates, key debt ratios, and the currency composition of long-term debt for all countries reporting through the Debtor Reporting system. A pocket edition of the Global Development Finance 2006, Volume II: Summary and Country Tables, it contains statistical tables for 135 countries as well as summary tables for regional and income groups